The social costs of crime in Mexico City and suburban areas - Villoro, Renata; Teruel, Graciela (Estudios Económicos de El Colegio de México, 2004)
In this paper we measure social costs of crime, following two approaches. First, estimate costs of homicides, at the National level in 1997, under different assumptions about lost wages. When assuming profiles differ over the life cycle, the costs amount from .03 to .6 percent of GDP, depending on the discount factor. Second, we take into consideration other types of crime to estimate social costs of crime in Mexico City. We found costs approximate 3.6 percent of the City's GDP, but consider this figure a lower bound. Further data including costs borne by non-victims would be most helpful for further research in this field.